Advances in radiotherapy enhancing the efficacy of immune checkpoint inhibitors in malignant - Liao, Yao; Deng, Jinjing; Yang, Xiyue; Wang, Decai; Du, Xiaobo (Frontiers in Oncology, 2025)
The introduction of immune checkpoint inhibitors (ICIs) has facilitated the elucidation of the mechanisms underlying the remote effects observed in tumor therapy and has demonstrated significant promise for treating several advanced tumors. However, the natural resistance of “cold tumors” remains a challenge that ICIs alone cannot overcome. Radiotherapy (RT) has been shown to enhance anti-tumor immunity by generating in situ antigens or antigenic fragments derived from tumor cells and local immune cell DNA, thereby attracting more immune-presenting cells to the tumor site. This process promotes the conversion of immune cells into anti-tumor effector cells and enhances the efficacy of ICIs, most likely reflecting the mechanism of the abscopal effect (ABE). Alternatively, ABE achieves optimal efficacy when anti-tumor effects synergistically enhance systemic immunity. This review delineates the molecular mechanisms underlying the distant compartment effect and summarizes clinical studies on enhancing immune checkpoint inhibitors through various RT techniques.